2015
DOI: 10.2147/ott.s80945
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue-secreted miR-27a promotes liver cancer by targeting FOXO1 in obese individuals

Abstract: The current notion that obesity is a major risk factor for the development of and the mortality associated with a subset of liver cancer is well appreciated. However, detailed mechanistic insights underlying this relationship are lacking. Better understanding of the adipose tissue-secreted miRNAs that play a potential role in defining primary liver cancer development and mediating the obesity-cancer communication offers the potential for new insights into tumor growth and interventions to modulate tumor format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 38 publications
(35 reference statements)
0
32
1
Order By: Relevance
“…miRNA negatively regulate gene expression at the post-transcriptional level via binding to the 3′-untranslated region of target mRNA. Although human FoxO1 and mouse FoxO1 are targeted by miR-27a (39,40) , there is no evidence that porcine FoxO1 is a target of miR-27a, as leucine (4 mM) down-regulated both the expression of miR-27a and the protein expression of FoxO1 in this study.…”
Section: Discussioncontrasting
confidence: 67%
“…miRNA negatively regulate gene expression at the post-transcriptional level via binding to the 3′-untranslated region of target mRNA. Although human FoxO1 and mouse FoxO1 are targeted by miR-27a (39,40) , there is no evidence that porcine FoxO1 is a target of miR-27a, as leucine (4 mM) down-regulated both the expression of miR-27a and the protein expression of FoxO1 in this study.…”
Section: Discussioncontrasting
confidence: 67%
“…First, the sample size included was relatively small. Second, Karolina and colleagues reported that there was an association of miR-27a and patients with metabolic syndrome (37), and Sun and colleagues reported that adipose tissue could secreted miR-27a to promote liver cancer by targeting FOXO1 (38), which means miR-27a is significantly associated with metabolic diseases and cancers. Although there was no patients with colorectal cancer with metabolic syndrome or patients with type 2 diabetes enrolled in our study, further studies with a large number of subjects ought to consider these cofounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…Ikzf1 can induce FoxO1, which activates Ebf1 and Pax5 transcription, leading to sustained commitment to the B cell lineage [49,50]. Additionally, FoxO1 has been shown to be a direct target of miR-27a in several nonhematopoietic cell types [51][52][53][54][55]. We examined expression of Ikzf1 in Lin 2 progenitor cultures and observed that loss of mirn23a results in an ;1.75-fold overexpression of Ikzf1 (Fig.…”
Section: Mirn23a Regulates B Lymphocyte Gene-expression Networkmentioning
confidence: 98%